On the halo-mass and radial scale dependence of the lensing is low effect. Issue 2 (23rd January 2021) - Lange, Johannes U; Leauthaud, Alexie; Singh, Sukhdeep; Guo, Hong; Zhou, Rongpu; Smith, Tristan L; Cyr-Racine, Francis-Yan
ABSTRACT: The canonical Lambda cold dark matter (ΛCDM) cosmological model makes precise predictions for the clustering and lensing properties of galaxies. It has been shown that the lensing amplitude of galaxies in the Baryon Oscillation Spectroscopic Survey (BOSS) is lower than expected given their clustering properties. We present new measurements and modelling of galaxies in the BOSS LOWZ sample. We focus on the radial and stellar mass dependence of the lensing amplitude mismatch. We find an amplitude mismatch of around $35{{\ \rm per\ cent}}$ when assuming ΛCDM with Planck Cosmological Microwave Background (CMB) constraints. This offset is independent of halo mass and radial scale in the range M halo ∼ 10 13.3 −10 13.9 h −1 M⊙ and $r=0.1\!-\!60 \, h^{-1} Mpc$ ($k ≈ 0.05\!-\!20 \, h \, {\rm Mpc}^{-1}$ ). The observation that the offset is both mass and scale independent places important constraints on the degree to which astrophysical processes (baryonic effects, assembly bias) can fully explain the effect. This scale independence also suggests that the 'lensing is low' effect on small and large radial scales probably have the same physical origin. Resolutions based on new physics require a nearly uniform suppression, relative to ΛCDM predictions, of the amplitude of matter fluctuations on these scales. The possible causes of this are tightly constrained by measurements of the CMB and of the low-redshift expansion history.